The association between muscular strength and depression in Korean adults: a cross-sectional analysis of the sixth Korea National Health and Nutrition Examination Survey (KNHANES VI) 2014 - Mee-Ri Lee; Sung Min Jung; Hyuk Bang; Hwa Sung Kim; Yong Bae Kim (BMC, 2018)
Abstract Background There are conflicting researches on the relationship between muscular strength and depression, the most common mental illness. There is no study of relationship between muscular strength and depression using national data from young adults to seniors. For example, there has not been a study done explaining mediating pathways among the influences of handgrip strength on depression. Here, we conducted survey for the association between relative handgrip strength and depression and explain mediated pathways for quality of life. Methods A cross-sectional study was administered to 4298 Korean adult subjects, aged 19-80 years, based on the 6th Korean National Health and Nutrition Examination Survey (KNHANES VI) of 2014. Handgrip strength reported as the average with each hand. The relative handgrip strength is defined as the handgrip strength divided by the body mass index (BMI). We performed analysis for all subjects and age groups (young adult, middle-aged, and elderly). We analyzed the association using multivariate linear regression and logistic regression. We also conducted mediation analysis for quality of life, which was measured by the EuroQol Five-Dimension Questionnaire (EQ5D). Results After adjusting for covariates, handgrip strength was inversely associated with the PHQ-9 score (P < 0.05). The odds ratios (OR) of depression symptoms were statistically significant for participants in the first and second quartile of handgrip strength compared to those with the highest quartile in entire sample, young adult, middle-aged, and elderly. There was about a 50% mediation effect of EQ5D in the relationship between handgrip strength and depression. Conclusions Using a large national sample, our results found that lower handgrip strength is associated with an increased risk of depression in Korean adult (young adult, middle-aged, and elderly). Our results suggest that increasing muscular strength may prevent depression in Korean adults.